Chest physiotherapy: an important adjuvant in critically ill mechanically ventilated patients with COVID-19 (2020)
In late 2019, an outbreak of a novel human coronavirus causing respiratory disease was identified in Wuhan, China. The virus spread rapidly worldwide, reaching pandemic status. Chest computed tomography scans of patients with coronavirus disease-2019 (COVID-19) have revealed different stages of respiratory involvement, with extremely variable lung presentations, which require individualized ventilatory strategies in those who become critically ill. Chest physiotherapy has proven to be effective for improving long-term respiratory physical function among ICU survivors. The ARIR recently reported the role of chest physiotherapy in the acute phase of COVID-19, pointing out limitation of some procedures due to the limited experience with this disease in the ICU setting. Evidence on the efficacy of chest physiotherapy in COVID-19 is still lacking. In this line, the current review discusses the important role of chest physiotherapy in critically ill mechanically ventilated patients with COVID-19, around the weaning process, and how it can be safely applied with careful organization, including the training of healthcare staff and the appropriate use of personal protective equipment to minimize the risk of viral exposure.